Comparative Genomic Analysis of Staphylococcus haemolyticus Reveals Key to Hospital Adaptation and Pathogenicity - Pain, Maria; Hjerde, Erik; Klingenberg, Claus; Cavanagh, Jorunn Pauline (Frontiers in Microbiology, 2019)
Staphylococcus haemolyticus is a skin commensal gaining increasing attention as an emerging pathogen of nosocomial infections. However, knowledge about the transition from a commensal to an invasive lifestyle remains sparse and there is a paucity of studies comparing pathogenicity traits between commensal and clinical isolates. In this study, we used a pan-genomic approach to identify factors important for infection and hospital adaptation by exploring the genomic variability of 123 clinical isolates and 46 commensal S. haemolyticus isolates. Phylogenetic reconstruction grouped the 169 isolates into six clades with a distinct distribution of clinical and commensal isolates in the different clades. Phenotypically, multi-drug antibiotic resistance was detected in 108/123 (88%) of the clinical isolates and 5/46 (11%) of the commensal isolates (p <0.05). In the clinical isolates, we commonly identified a homolog of the serine-rich repeat glycoproteins sraP. Additionally, three novel capsular polysaccharide operons were detected, with a potential role in S. haemolyticus virulence. Clinical S. haemolyticus isolates showed specific signatures associated with successful hospital adaption. Biofilm forming S. haemolyticus isolates that are resistant to oxacillin (mecA) and aminoglycosides (aacA-aphD) are most likely invasive isolates whereas absence of these traits strongly indicates a commensal isolate. We conclude that our data show a clear segregation of isolates of commensal origin, and specific genetic signatures distinguishing the clinical isolates from the commensal isolates. The widespread use of antimicrobial agents has probably promoted the development of successful hospital adapted clones of S. haemolyticus clones through acquisition of mobile genetic elements or beneficial point mutations and rearrangements in surface associated genes.